2013
DOI: 10.1111/mec.12547
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the insectivorous batPipistrellus nathusiiduring autumn migration and summer residence

Abstract: Migration is widespread among vertebrates, yet bat migration has received little attention and only in the recent decades has a better understanding of it been gained. Migration can cause significant changes in behaviour and physiology, due to increasing energy demands and aerodynamic constraints. Dietary shifts, for example, have been shown to occur in birds before onset of migration. For bats, it is not known if a change in diet occurs during migration, although breeding season-related dietary preference has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 86 publications
(91 reference statements)
1
45
0
Order By: Relevance
“…The animal prey detected visually in Black Wheatear faeces was in line with previous studies (Hodar, ; Prodon, ; Richardson, ), showing a prevalence for Hymenoptera, mainly Formicidae, and Coleoptera, Hemiptera, Araneae and Diptera. As expected, these groups were largely recovered through molecular analysis, though metabarcoding yielded a much larger diversity of prey and higher taxonomic resolution, particularly in the case of the COI marker ZBJ (Hope et al, ; Krüger, Clare, Greif, et al, ; Krüger, Clare, Symondson, Clare, Symondson, Keišs, & Pētersons, ; Razgour et al, ). Furthermore, some taxa were far more often detected through metabarcoding than by visual examination, including orders that seemed to be important in the diet such as Lepidoptera and Orthoptera.…”
Section: Discussionmentioning
confidence: 78%
“…The animal prey detected visually in Black Wheatear faeces was in line with previous studies (Hodar, ; Prodon, ; Richardson, ), showing a prevalence for Hymenoptera, mainly Formicidae, and Coleoptera, Hemiptera, Araneae and Diptera. As expected, these groups were largely recovered through molecular analysis, though metabarcoding yielded a much larger diversity of prey and higher taxonomic resolution, particularly in the case of the COI marker ZBJ (Hope et al, ; Krüger, Clare, Greif, et al, ; Krüger, Clare, Symondson, Clare, Symondson, Keišs, & Pētersons, ; Razgour et al, ). Furthermore, some taxa were far more often detected through metabarcoding than by visual examination, including orders that seemed to be important in the diet such as Lepidoptera and Orthoptera.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, migratory bats do not seem to consume large numbers of insects during migration flights. Since others and we observed migratory bats defecating shortly after they were captured at our study site [49], we speculate that migratory bats may hunt insects before they launch for long-distance migratory flights. We only observed a trend for a higher proportion of FB in relation to echolocation calls when the green light was switched on compared to darkness, suggesting that the feeding activity of P .…”
Section: Discussionmentioning
confidence: 92%
“…Krüger et al. () suggested that all factors play a role; however, this cannot be proved, as prey availability, for example, was not evaluated.…”
Section: Resultsmentioning
confidence: 99%